Sex and gender bias in chronic coronary syndromes research: analysis of studies used to inform the 2019 European Society of Cardiology guidelinesResearch in context - Kathleen Bastian-Pétrel; Jessica L. Rohmann; Sabine Oertelt-Prigione; Marco Piccininni; Katja Gayraud; Michelle Kelly-Irving; Nathalie Bajos (Elsevier, 2024)
Summary: Background: Sex and gender inequalities in ischemic heart diseases persist. Although ischemic heart disease is less common in women, they experience worse clinical outcomes and are less likely to receive guideline-recommended treatments. The primary scientific literature from which clinical guideline recommendations are derived may not have considered potential sex- and gender biases. This study aims to determine whether the literature cited in recent cardiovascular guidelines' clinical recommendations contain sex and gender biases. Methods: We analysed publications cited in the 2019 European Society of Cardiology (ESC) guideline recommendations on chronic coronary syndromes, using a checklist to guide data extraction and evaluate the individual studies for sex- and gender-related aspects, such as inclusion/exclusion criteria, outcome measures, and demographic data reporting. To assess representation over time, the proportion of women participants in each study was computed and analysed using a beta regression model. We also examined the associations between women's representation, journal impact factor and author gender. Findings: Among the 20 ESC recommendations on chronic coronary syndromes, four contained sex-related statements; we did not identify any gender-specific suggestions. The referenced literature upon which these recommendations were based consisted of 108 articles published between 1991 and 2019, encompassing more than 1.6 million study participants (26.8%; 432,284 women). Only three studies incorporated sex-sensitive designs; none were gender-specific. The term "gender" did not occur in 84% (n = 91/108) of the publications; when used, it was exclusively to denote biological sex. The proportion of women (assumed by investigators) among study participants fluctuated over time. Having a woman as first (odds ratio (OR) = 1.68, 95% CI: 1.19-2.39) or last author (OR = 2.28, 95% CI: 1.31-3.97), was significantly associated with having more women participants in the study. Interpretation: The data underlying ESC guideline recommendations largely lack reporting of possible sex- and gender-specific aspects, and women are distinctly underrepresented. To what extent these recommendations apply to members of specific population groups who are not well-represented in the underlying evidence base remains unknown. Funding: This study is part of the Gender and Health Inequalities (GENDHI) project, ERC-2019-SyG. This project has received funding from the European Research Council (ERC).